2018
DOI: 10.18203/2349-3933.ijam20183910
|View full text |Cite
|
Sign up to set email alerts
|

Medical problems in children with Down syndrome

Abstract: Background: Down syndrome (DS) is a major cause of mental retardation of prenatal origin and has several associated co-morbidities involving cardiovascular system, respiratory, endocrine system, hematological, gastrointestinal, musculoskeletal, eye and ear defects, immunological changes and neurological system. This study was conducted to identify the common medical problems in children with Down syndrome and the morbidity associated with these conditions. The objective of the present study was to find out the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Global developmental delay is predicted occur in children with DS, which affects motor, cognitive, language, and personal skills [25], [26]. This is in accordance with research in Aoki et al [26] which showed that the speed of development of children with DS was found to be slower than that of children with DS.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Global developmental delay is predicted occur in children with DS, which affects motor, cognitive, language, and personal skills [25], [26]. This is in accordance with research in Aoki et al [26] which showed that the speed of development of children with DS was found to be slower than that of children with DS.…”
Section: Discussionsupporting
confidence: 78%
“…This delay is associated with the large number of comorbidities present in children with DS [26]. Vadakedom et al [25] in their study found that most of the samples were globally delayed with hypotonic conditions. Delays in motor area in children with DS are predictable related to hypotonia conditions that occur in children with DS, including primitive reflexes and joint hypermobility that affect the ability to control posture so that they play role in movement and motor coordination.…”
Section: Discussionmentioning
confidence: 96%
“…Multisystemic involvement including thyroid dysfunction can cause significant morbidity if left untreated. [15] The thyroid hormone plays a vital role in metabolism, growth and development of children, especially in infancy. [16] The clinical presentation of hypothyroidism in an older child can be missed, as the signs and symptoms can overlap with that of DS.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence is 1/750–1/1,100 live births [2]. Congenital malformations generally interest heart and gastrointestinal tract [3, 4]. Major brain abnormalities and hydrocephalus are extremely rare [5].…”
Section: Discussionmentioning
confidence: 99%